Gene expression defines natural changes in mammalian lifespan. Issue 3 (9th February 2015) - Fushan, Alexey A.; Turanov, Anton A.; Lee, Sang‐Goo; Kim, Eun Bae; Lobanov, Alexei V.; Yim, Sun Hee; Buffenstein, Rochelle; Lee, Sang‐Rae; Chang, Kyu‐Tae; Rhee, Hwanseok; Kim, Jong‐So; Yang, Kap‐Seok; et al.
Summary Mammals differ more than 100‐fold in maximum lifespan, which can be altered in either direction during evolution, but the molecular basis for natural changes in longevity is not understood. Divergent evolution of mammals also led to extensive changes in gene expression within and between lineages. To understand the relationship between lifespan and variation in gene expression, we carried out RNA‐seq‐based gene expression analyses of liver, kidney, and brain of 33 diverse species of mammals. Our analysis uncovered parallel evolution of gene expression and lifespan, as well as the associated life‐history traits, and identified the processes and pathways involved. These findings provide direct insights into how nature reversibly adjusts lifespan and other traits during adaptive radiation of lineages.